Mengembalikan Kewibawaan Mahkamah Agung Sebagai Peradilan Yang Agung - Dudu Duswara Machmudin (The Constitutional Court of the Republic of Indonesia, 2013)
Authority, protection, legal certainty and justice are absolute requirements for a country which is based on law. All judges should endeavor to harmonize justice based on the provisions of law (legal justice), justice based on morality (moral justice) and justice based on the will of the people (social justice). Supreme Court as the highest of all courts in the country should be filled with Justices who act as the reformer of law to realize clean court. The great authorities and duties the justices have require a high degree of responsibility in order that the decisions issued are for the sake of justice and in the Name of God Almighty. This denotes that law enforcement, truth and justice must be accounted for either to human or God. Supreme Court Justices are expected to integrate the three concept of justices in order that harmonization of legal responsibility and social satisfaction which is built on morality based on goodness and badness as the standard can be realized. As the Reformer of law, Supreme Court Justice should be able and have the courage to make breakthrough which is not against the law and social justice and the morality itself.